The Need for a Global Ocean Vision Within Biodiversity Beyond National Jurisdiction: A Key Role for Strategic Environmental Assessment - Ferreira, Maria Adelaide; Johnson, David E.; Andrade, Francisco (Frontiers in Marine Science, 2022)
An ecosystem-based forward-looking vision for the global ocean, encompassing ocean health and productivity, ecosystem integrity and resilience, incorporating area beyond national jurisdiction, is fundamental. A vision which is holistic and universally acceptable to guide future sustainable ocean policies, plans and programmes (PPPs). We argue that Strategic Environmental Assessment (SEA) is the best available framework to develop such a vision and its suitability for this purpose should be recognised within the on-going process to negotiate an International Legally Binding Instrument (ILBI) for the conservation and sustainable use of Biodiversity Beyond National Jurisdiction (BBNJ Agreement). This perspective paper justifies why such an ecosystem-based Global Ocean Vision is essential. It then describes the key characteristics it must integrate and how it can be elaborated in the framework of a collective SEA within the BBNJ process. We advocate expanding text in Part I General Provisions of the draft BBNJ Agreement to include development of such a global ocean vision. We conclude by highlighting the opportunity and timeliness of this proposal, with the fifth session of the IGC of BBNJ tentatively scheduled for August 2022.